On which groups can arise as the canonical group of a spherical latin bitrade - Bonetta-Martin, Kyle (Ars mathematica contemporanea, 2017)
We address a question of Cavenagh and Wanless asking: which finite abelian groups arise as the canonical group of a spherical latin bitrade? We prove the existence of an infinite family of finite abelian groups that do not arise as canonical groups of spherical latin bitrades. Using a connection between abelian sandpile groups of digraphs underlying directed Eulerian spherical embeddings, we go on to provide several, general, families of finite abelian groups that do arise as canonical groups. These families include: (1) any abelian group in which each component of the Smith Normal Form has composite order; (2) any abelian group with Smith Normal Form ?$\mathbb{Z}_{p}^{n} (\oplus_{i = 1}^{k}\mathbb{Z}_{pa_{i}})$?, where ?$1 ≤ k$?, ?$2 ≤ a_{1},a_{2},…,a_{k},p$? and ?$n ≤ 1 + 2\sum_{i = 1}^{k}(a_{i} - 1)$?; and (3) with two exceptions and two potential exceptions any abelian group of rank two.
Keywords: abelska sipinska grupa; kanonična grupa; sferični par latinskih kvadratov